Pengaruh Ekstrak Biji Durian dan Oksifluogen 240 g/L Terhadap Kematian Gulma di Perkebunan Kelapa Sawit - Rama Sitinjak; Reza Surbakti; Gresia Sagala; Lawisto Brutu (Universitas Sam Ratulangi, 2023)
This study aims: (1) to determine the effect of crude extract of durian seeds on weed control in oil palm plantations, (2) to determine the effect of the herbicide oxyfluogen 240 g/L which is effective on weed control in oil palm plantations, (3) to determine the effect of interaction of crude extract of durian seeds and oxyfluogen herbicide on weeds in oil palm plantations. The method used in this study was a randomized block design with a factorial pattern. The first factor was durian seed extract (D) with a concentration consisting of 4 levels, namely: control (D0), 100 ml/L (D1), 200 ml/L (D2), 400 ml/L (D3). The second factor is the herbicide oxyfluogen (O) with a concentration consisting of 4 levels, namely: control (o0), 1 ml/L (O1), 2 ml/L (O2), 3 ml/L (O3). From these 2 factors, 16 treatments were obtained with 2 replications, and the number of samples was 32 sample plots, plot area 1 m2, distance between replicates 1 m from 2 factors. The results of data analysis showed that administration of durian seed extract and administration of oxyfluogen had a very significant effect on the percentage of weed mortality in oil palm plantations, but the interaction had no significant effect on the first week and second week after application. The best treatment was the application of a combination of 400 ml/L of durian seed extract with 3 ml/L of oxyfluogen which killed the highest weeds around 81% after two weeks of application. Durian seed extract has potential as a bioherbicide, which can be used as an alternative technique in weed control systems in oil palm plantations.